Market Facilitation by Local Government and Firm Efficiency : Evidence from China - Cull, Robert; Xu, Lixin Colin; Yang, Xi; Zhou, Li-An; Zhu, Tian (World Bank, Washington, DC, 2014)
This paper uses data from a large survey of Chinese firms to investigate whether local government efforts to facilitate market development improve firm efficiency. Both government provision of information about products, markets, and innovation and government assistance in arranging loans are positively associated with firm efficiency. Those private firms with weak access to and knowledge of financial, input, and product markets benefit most from such assistance. These patterns are robust across multiple estimation approaches. Case studies of specific types of market facilitation by local governments are provided. The evidence is consistent with the notion that government facilitation can help some firms overcome market failures in the early stages of development. The paper argues that changing fiscal dynamics that forced local governments to become increasingly self-reliant in generating revenue and a government promotion system based on local economic performance compelled these efforts at market facilitation.